PENGARUH HASIL BELAJAR MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 1 PEKANBARU - Rozi Oqtria Sari; Sumarno '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effect of the interest in entrepreneurship learning outcomes of students of class XI TKJ SMK 1 Pekanbaru . This research was conducted in SMK Negeri 1 Pekanbaru from December 2015 through January 2016. The research method used is descriptive quantitative method . A population of 64 students and a sample of 64 students. Data collection instruments used were questionnaires were processed using a Likert scale for dependent variables : interest in entrepreneurship ( Y ) ; documentation used for the independent variables : the learning outcomes ( X ) . The data analysis technique used is simple linear regression statistical techniques . From the results , it can be concluded that : ( 1 ) the learning outcomes affect the interest in entrepreneurship ; ( 2 ) the influence of the learning outcomes of the interest in entrepreneurship is 28,8 .Keywords : Influence , the result of learning , interest in entrepreneurship.